The B-Box Domain Protein BBX21 Promotes Photomorphogenesis(1) - Xu, Dongqing (Plant Physiol, 2018)
B-box-containing (BBX) proteins play critical roles in a variety of cellular and developmental processes in plants. BBX21 (also known as SALT TOLERANCE HOMOLOG2), which contains two B-box domains in tandem at the N terminus, has been previously demonstrated as a key component involved in the COP1-HY5 signaling hub. However, the exact molecular and physiological roles of B-box domains in BBX21 are largely unclear. Here, we found that structurally disruption of the second B-box domain, but not the first one, in BBX21 completely abolishes its biological and physiological activity in conferring hyperphotomorphogenetic phenotype in Arabidopsis (Arabidopsis thaliana). Intact B-box domains in BBX21 are not required for interaction with COP1 and its degradation by COP1 via the 26S proteasome system. However, disruption of the second B-box of BBX21 nearly impairs its ability for binding of T/G-box within the HY5 promoter both in vitro and in vivo, as well as controlling HY5 and HY5-regulated gene expression in Arabidopsis seedlings. Taken together, this study provides a mechanistic framework in which BBX21 directly binds to the T/G-box present in the HY5 promoter possibly through its second B-box domain, which in turn controls HY5 and HY5-regulated gene expression to promote photomorphogenesis.